(untitled) (Medico Legal Update, 2020)
Introduction: Biomedical waste (BMW) collection and proper disposal have become a substantial issue for both the general and the medical community. In the present-day scenario, approximately 25% of biomedical waste is found to be hazardous and may affect the health of both general community and medical personnel. Medical students as future professionals are soon going to be an integral part of health care system. They should have proper and sufficient knowledge on BMW management. Moreover, the awareness about various aspects of BMW management has to be assessed frequently too. Objective: The objective of the study was to assess the awareness of know on biomedical waste management at tertiary care hospital, (Saveetha Medical College) among medical students. Methodology: This was a cross-sectional study done at Saveetha Medical College and Hospital. A total of 100 MBBS students were included in the study with their prior consent. A pre tested semi structured questionnaires was given to participants. The data was analyzed using software SPSS. Results: 53% were boys and 47% were girl students. Among various questions asked in the Questionnaire, the overall knowledge on the awareness of biomedical waste disposal among medical students was 46.8%. Conclusion: There is a lack of appropriate knowledge about biomedical waste management, awareness and practices of proper waste disposal. Hence, there is a need of training and programmes regarding health care waste management.